Towards Greater Understanding of the Role of Eating and Moving Behaviours in Wellbeing - Maclaren, Olivia (Auckland University of Technology, 2019)
New Zealand’s public health system is primarily deficit-based; that is, the focus is mainly on disease prevention and treatment. Increasing levels of morbidity (time spent in poor health) and the failure of the current system to improve these outcomes, has led to a call for a reorientation of perspective. Positive health provides a framework for such a paradigm shift by changing the emphasis away from disease treatment and prevention towards one of optimising wellbeing. By emphasising a more holistic approach to improve the overall functioning of individuals this approach arguably has the potential to improve the health and wellbeing of the population and address the short-comings of the deficit-based system. Further research is required to provide a greater weight of evidence in support of the practical application of a positive health paradigm. It is known that eating a healthy diet and living a physically active life are key factors in the maintenance of physical and mental health as well as improved wellbeing. Historically the examination and prescription of both nutrition and physical activity at a population level has been limited in its focus and centred on disease risk. Nutritional science has predominantly focused on the calorie content, and macronutrient and nutrient-specific effects on varied biomarkers of physical health. Physical activity epidemiological research has predominantly focused on the energy expenditure or time needed to elicit a positive cardiometabolic response. What this historical dose-response methodology has failed to address is that both nutrition and physical activity are multifaceted behaviours. Furthermore in the ‘real-world’ people eat food, not nutrients, and the majority of people move and participate in activities rather than consider the time and intensity of their movement. The overarching aims of this thesis were to explore broad patterns and contexts to nutrition and physical activity behaviours and examine their relationship to wellbeing. An additional aim was to move towards a greater understanding of the practical applications of lifestyle behaviours to a positive health (wellbeing) framework. This thesis is comprised of five studies. In Study 1, a novel online survey tool was developed to enable a broader investigation into nutrition and physical activity behaviours. Content validity of the survey was assessed by an expert panel of nutrition and physical activity specialists and through participant feedback during the piloting of the survey. Test-retest reliability of the repeated measures online pilot survey (n = 22) assessed question response agreement. Test-retest reliability showed fair (0.40 – 0.75) to perfect (1.00) strength of agreement (Cohen’s weighted kappa) for 38 of the 40 items. In Study 2, the validated survey tool was integrated into the larger Sovereign Wellbeing Index survey (SWI; round 2: 2014; N = 10,012). The observational, cross-sectional data obtained were then used to develop a novel profiling system for a range of dietary patterns. Profiles were developed using an a-priori process designed to differentiate popular eating approaches. The prevalence of the varied nutrition profiles was also described: Junk Food (22.4%, 95% CI [21.6, 23.3]), Moderator (43.0% [42.1, 44.0]), High-Carbohydrate (23.0% [22.2, 23.8]), Mediterranean (11.1% [10.5, 11.8]), Flexitarian (8.8% [8.2, 9.4]), and Low-Carbohydrate (5.4% [4.9, 5.8]). The results showed that New Zealanders followed a broad range of eating patterns with the majority following some form of ‘healthful’ pattern. In Study 3, physical activity behaviours were explored across different exercise types, environmental and social contexts; additionally, clustering patterns were observed. When the SWI population sample was again examined, 80.2% (n= 8026) did some form of exercise weekly. The most prevalent type of exercise was moderate intensity (90.7%, 95% CI [90.0, 91.3]), outdoors in a natural setting was the most popular venue (58.5% [57.4, 59.6], and most respondents exercised on their own (87.9% [87.1, 88.6]. Two-step cluster analysis showed the type of exercise participated in was in four distinct exercise clusters (Mixed Activity n= 3039, 32.6%; Moderate Intensity n= 2873, 30.8%; Sport n= 1924, 20.6%; Non-Exercise n= 1490, 16.0%; named based on their predominant exercise type). This study highlighted the diverse contexts to how New Zealanders carried out their exercise. The final study, Study 4, explored wellbeing differences (one-way analysis of variance) between the nutrition profiles and exercise clusters developed in the previous two studies. Wellbeing (Diener’s Flourishing Scale, Centre for Epidemiologic Studies Depression Scores) showed small but significant differences between nutrition profiles (partial-eta squared: ρη2= .017; ρη2= .027), exercise clusters (ρη2 = .025; ρη2 = .016) and nutrition-exercise combinations (ρη2= .039; ρη2= .043). A Mediterranean approach to eating was consistently more advantageous across both individual profiles and when combined with various exercise clusters (Mediterranean*Sport, Mediterranean*Mixed Exercise and Mediterranean*Moderate-Intensity). Whereas, Flexitarian, Junk Food and Non-Exercise approaches were consistently less advantageous to wellbeing especially in combination (Flexitarian*Non-Exercise and Junk Food*Non-Exercise). It appeared that a conscientious approach that included or restricted certain foods in some type of eating pattern was most advantageous for optimal wellbeing. Exercise of any type was valuable, but the inclusion of a high-intensity component was most beneficial. This thesis provides a substantial and original contribution to the body of knowledge in the fields of lifestyle behaviours and wellbeing. By exploring nutrition and physical activity in novel contexts, this new knowledge shows that New Zealanders eat and move in a variety of ways and that the patterns to these behaviours differ in their relationship to wellbeing. Moving and eating patterns that are outside of current governmental guidelines appear advantageous to wellbeing, and this suggests a review is needed of the current ideology around population prescription of moving and eating. This thesis is a step towards the practical application of promoting and implementing a positive health framework. This thesis also supports the contention that reorientation of the public health system towards a positive health framework is practicable and arguably necessary. Future work should consider the use of the profiles and clusters developed in this thesis to target specific groups for positive wellbeing interventions.
Keywords: Wellbeing; Nutrition; Physical activity; Epidemiology; New Zealand